2020
DOI: 10.4081/ejtm.2020.9353
|View full text |Cite
|
Sign up to set email alerts
|

Perceived fatigue, lower limb muscle force and performance fatigability after a rehabilitation program in Multiple Sclerosis

Abstract: Muscle weakness and fatigue represent frequent disabling symptoms for Multiple Sclerosis (MS) patients. We evaluated the effects of an intensive task-oriented circuit training (TOCT) on perceived fatigue, muscle strength and changes in motor performance fatigability in mildly impaired MS patients. Fifteen MS patients performed different functional scales, self-reported questionnaires and instrumental evaluations before (T0) and after (T1) TOCT. Strength and performance fatigability were analyzed during isometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Rehabilitation interventions have shown potential for enhancing maximal neural drive during knee extensions, as indicated by integrated EMG measures 86 . However, no significant changes were observed in mechanical and electrical fatigue after two weeks of rehabilitation, despite higher force output 87 . Table 1 summarises the main clinical findings when using time-series biosignals, namely EEG, IMU, and EMG data.…”
Section: Emgmentioning
confidence: 73%
See 1 more Smart Citation
“…Rehabilitation interventions have shown potential for enhancing maximal neural drive during knee extensions, as indicated by integrated EMG measures 86 . However, no significant changes were observed in mechanical and electrical fatigue after two weeks of rehabilitation, despite higher force output 87 . Table 1 summarises the main clinical findings when using time-series biosignals, namely EEG, IMU, and EMG data.…”
Section: Emgmentioning
confidence: 73%
“…Similar to the collection of IMU data for MS monitoring, walking tasks have been used to collect EMG 72,[79][80][81][82][83] . Furthermore, popular were contraction and extensions tasks [84][85][86][87] as well as reaching tasks 88,89 . EMG sensors have also been used to investigate dysphagia [90][91][92] .…”
Section: Emgmentioning
confidence: 99%
“…The results of this study follow a positive trend similar to the already published data of Chisari et al ( 33 ), in which a group of 17 patients with MS showed significant improvement in the TUG test and a positive trend in the SF-36 questionnaire. In another study published by Tramonti et al ( 14 , 15 ), a group of 15 patients with MS showed only an insignificant trend in TUG test, but a clear improvement in the MFIS and MSWS-12 questionnaires. However, both studies were more task-oriented and lacked a control group.…”
Section: Discussionmentioning
confidence: 87%
“…There is moderate evidence that circuit class therapy is effective in improving mobility for people after stroke; they may be able to walk further, faster, and with more independence and confidence in their balance. The effectiveness of circuit class therapy on walking ability in patients with MS has been demonstrated in a small number of patients ( 12 , 13 , 14 , 15 ). In addition, circuit class therapy reduces the high demands on physiotherapists in conventional one-on-one exercise, and may therefore be made available to more patients.…”
mentioning
confidence: 99%